Analisis Efisiensi Antara Motor Listrik Induksi Dengan Mesin Diesel Sebagai Penggerak Pompa Air Sungai - Jayeng Maulana; Arief Budi Laksono (Jurnal JEETech, 2022)
In the development of technology in this digital era, mankind will be more advanced in terms of electronics, so that it can facilitate work and human activities in daily life, not only in terms of technology and artificial intelligence, humans in this modern era will need resources to turn on and run tools as a helper for work and daily life. The conclusion from the above research can be concluded, the power required to drive the water pump with maximum results is 3.58 Kw, the volume of water transfer at 1500rpm water pump = 15.6m3/hour, water height if tested for 1 hour: t = 15.6 / (5.5 × 8) = 0.35 m, estimated electric motor power consumption = 0.55kWh, then electric motor power consumption = 2.4kw/hour, Electric motor operating costs: Rp3465/hour, estimated consumption diesel engine fuel according to data from specifications is 294g/kWh, diesel engine power consumption = 520ml/hour, electric motor operating costs = Rp3465/hour, diesel engine operating costs = Rp2668/hour..